Scoping systematic review of treatments for eczema - Nankervis, Helen; Thomas, K.S.; Delamere, Finola M.; Barbarot, Sebastien; Rogers, Natasha K.; Williams, Hywel C. (NIHR Journals Library, 2016)
Background: Eczema is a very common chronic inflammatory skin condition. Objectives: To update the National Institute for Health Research (NIHR) Health Technology Assessment (HTA) systematic review of treatments for atopic eczema, published in 2000, and to inform health-care professionals, commissioners and patients about key treatment developments and research gaps. Data sources: Electronic databases including MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Skin Group Specialised Register, Latin American and Caribbean Health Sciences Literature (LILACS), Allied and Complementary Medicine Database (AMED) and Cumulative Index to Nursing and Allied Health Literature (CINAHL) were searched from the end of 2000 to 31 August 2013. Retrieved articles were used to identify further randomised controlled trials (RCTs). Review methods: Studies were filtered according to inclusion criteria and agreed by consensus in cases of uncertainty. Abstracts were excluded and non-English language papers were screened by international colleagues and data were extracted. Only RCTs of treatments for eczema were included, as other forms of evidence are associated with higher risks of bias. Inclusion criteria for studies included availability of data relevant to the therapeutic management of eczema; mention of randomisation; comparison of two or more treatments; and prospective data collection. Participants of all ages were included. Eczema diagnosis was determined by a clinician or according to published diagnostic criteria. The risk of bias was assessed using the Cochrane Collaboration risk-of-bias tool. We used a standardised approach to summarising the data and the assessment of risk of bias and we made a clear distinction between what the studies found and our own interpretation of study findings. Results: Of 7198 references screened, 287 new trials were identified spanning 92 treatments. Trial reporting was generally poor (randomisation method: 2% high, 36% low, 62% unclear risk of bias; allocation concealment: 3% high, 15% low, 82% unclear risk of bias; blinding of the intervention: 15% high, 28% low, 57% unclear risk of bias). Only 22 (8%) trials were considered to be at low risk of bias for all three criteria. There was reasonable evidence of benefit for the topical medications tacrolimus, pimecrolimus and various corticosteroids (with tacrolimus superior to pimecrolimus and corticosteroids) for both treatment and flare prevention; oral ciclosporin; oral azathioprine; narrow band ultraviolet B (UVB) light; Atopiclair™ and education. There was reasonable evidence to suggest no clinically useful benefit for twice-daily compared with once-daily topical corticosteroids; corticosteroids containing antibiotics for non-infected eczema; probiotics; evening primrose and borage oil; ion-exchange water softeners; protease inhibitor SRD441 (Serentis Ltd); furfuryl palmitate in emollient; cipamfylline cream; and Mycobacterium vaccae vaccine. Additional research evidence is needed for emollients, bath additives, antibacterials, specialist clothing and complementary and alternative therapies. There was no RCT evidence for topical corticosteroid dilution, impregnated bandages, soap avoidance, bathing frequency or allergy testing.